Protection of whistleblowers in Serbia: The role and importance of whistleblowers in revealing corruption - Tanjević Nataša (Trendovi u Poslovanju)
Corruption is a major problem, which is best demonstrated by the results in the fight against this negative phenomenon. In general, although a large number of factors are affected by the occurrence of corruption, one of the most significant is the probability of detecting corruption and finding appropriate penalties for such behavior. In this regard, the aim of this paper is to point out the role and significance of the 'whistleblowers' in the detection and prevention of corruption, bearing in mind that the disclosure of cases of corruption by 'whistleblowing' is one of the most effective means of combating this socially negative phenomenon. Finally, this paper points to the new normative solutions in our country intended to clarify the direction of reforming this area. It also points out the gaps which need to be analyzed in detail, based on the issues that appear in practice, and through appropriate future changes in regulations. It is crucial to determine specific solutions, so the problems could be identified and solved in a timely manner.